MTORC1 inhibition drives crinophagic degradation of glucagon - Sangam Rajak; Sherwin Xie; Archana Tewari; Sana Raza; Yajun Wu; Boon-Huat Bay; Paul M. Yen; Rohit A. Sinha (Elsevier, 2021)
Objective: Crinophagy is a secretory granule-specific autophagic process that regulates hormone content and secretion in endocrine cells. However, despite being one of the earliest described autophagic processes, its mechanism of action and regulation in mammalian cells remains unclear. Methods and results: Here, we examined mammalian crinophagy and its modulation that regulate hormone secretion in a glucagon-producing mouse pancreatic α-cell line, alpha TC1 clone 9 (αTC9), and in vivo. Western blot, electron microscopy, and immunofluorescence analyses were performed to study crinophagy and glucagon secretion in αTC9 cells and C57BL/6 mice, in response to the mammalian target of rapamycin complex 1 (MTORC1) inhibitor rapamycin. Amino acid depletion and pharmacological inhibition of MTORC1 increased the shuttling of glucagon-containing secretory granules into lysosomes for crinophagic degradation to reduce glucagon secretion through a macroautophagy-independent mechanism. Furthermore, MTORC1 inhibition reduced both intracellular and secreted glucagon in rapamycin-treated mice, in response to hypoglycaemia. Conclusion: In summary, we have identified a novel crinophagic mechanism of intracellular glucagon turnover in pancreatic α-cells regulated by MTORC1 signalling.